Kiemlicze pomogli. O Sienkiewiczowskich odniesieniach w prozie Karola Olgierda Borchardta - Rusin, Joanna (Tematy i Konteksty, 2015)
Born at the beginning of the 20th century, the popular Polish writer and captain of the Polish Merchant Marine, Karol Olgierd Borchardt, belonged to a generation brought up on the literary work of Henryk Sienkiewicz. "Potop" was Borchardt’s favourite novel, and Sienkiewicz his most acknowledged writer. Recalling his sailing at sea, especially in the novels "Znaczy kapitan" (1961) and "Szaman morski" (1985), Borchardt eagerly and frequently made references to characters and events from "Trylogia". Even in his unfinished book of childhood memories, "Pod czerwoną różą" (1991), published posthumously, while telling a family anecdote, Borchardt made references to Kiemlicze, known from "Potop". One may say that Borchardt remained faithful to Sienkiewicz for the rest of his life, invariably con amore referring to and citing the works of Sienkiewicz.